Zero Dollar Tourist: Analisis Kritis Diskursus Segmen Pasar Wisatawan Tiongkok dalam Pariwisata Bali - Gede Ginaya; Made Ruki; Ni Wayan Wahyu Astuti (Pusat Kajian Bali Universitas Udayana, 2019)
As an icon of national tourism, Bali has become a world-top tourist destination. In 2018, Bali gained an award from Trip Advisor as the world’s best tourist destination. It has helped Bali to boost the number of foreign tourist arrival including Chinese. However, the increase visitor of Chinese tourist has caused a dilemma between the quantity and quality tourists as it is shown by the current issue of zero-dollar tour. This article critically analyses discourse on Chinese tourist market segment and its challenges to realise tourism sustainable in Bali. Data were obtained by observation and in-depth interviews with stakeholders and from literature review. Discourse of power/knowledge, deconstruction, and communicative action theories were applied eclectically to undertake this study. The results revealed that a space of discussion to find solution for the problem faced on the discourse of Chinese tourist market segment are needed as this could contribute to realise sustainable tourism development in Bali.